Biogeographic drivers of diazotrophs in the western Pacific Ocean. (28th January 2019) - Chen, Mingming; Lu, Yangyang; Jiao, Nianzhi; Tian, Jiwei; Kao, Shuh‐Ji; Zhang, Yao
Abstract: The global budget of marine nitrogen (N) is not balanced, with N removal largely exceeding N fixation. One of the major causes of this imbalance is our inadequate understanding of the diversity and distribution of marine N2 fixers (diazotrophs) as well as their contribution to N2 fixation. Here, we performed a large‐scale cross‐system study spanning the South China Sea, Luzon Strait, Philippine Sea, and western tropical Pacific Ocean to compare the biogeography of seven major diazotrophic groups and N2 fixation rates in these ecosystems. Distinct spatial niche differentiation was observed. Trichodesmium was dominant in the South China Sea and western equatorial Pacific, whereas the unicellular cyanobacterium UCYN‐B dominated in the Philippine Sea. Furthermore, contrasting diel patterns of Trichodesmium nifH genes and UCYN‐B nifH gene transcript activity were observed. The heterotrophic diazotroph Gamma A phylotype was widespread throughout the western Pacific Ocean and occupied an ecological niche that overlapped with that of UCYN‐B. Moreover, Gamma A (or other possible unknown/undetected diazotrophs) rather than Trichodesmium and UCYN‐B may have been responsible for the high N2 fixation rates in some samples. Regional biogeochemistry analyses revealed cross‐system variations in N2 ‐fixing community composition and activity constrained by sea surface temperature, aerosol optical thickness, current velocity, mixed‐layer depth, and chlorophyll a concentration. These factors except for temperature essentially control/reflected iron supply/bioavailability and thus drive diazotroph biogeography. This study highlights biogeographical controls on marine N2 fixers and increases our understanding of global diazotroph biogeography.